Perancangan Decision Support System Penilaian Kinerja Dosen Berdasarkan Penilaian Prestasi Kerja Pegawai dan Beban Kinerja Dosen - Ramadhan, Rizal Furqan; Tolle, Herman; Muslim, Muhammad Aziz (MATICS, 2016)
The lecturer is one of the essentialcomponents in the Higher Education system. Performanceassessment of lecturer needs to be conducted to measurethe lecturer capability based on the Tri Darma’s HigherEducation concept. Related to the nowadays technologydevelopment, to conduct performance assessment oflecturer can use the Decision Support System based onseveral criteria as the assessment material. The providedcriteria in this paper seem to be the obtained criteria fromP2KP and BKD component. P2KP is performanceassessment of lecturer under the Badan KepegawaianNegara (BKN) supervision. Meanwhile BKD isperformance assessment of lecturer under the DIKTIsupervision. The lecturer criteria are taken from those twocomponents because the lecturers’ status cannot beseparated from the officer under BKN and educator underthe DIKTI support. It is expected that the criteria comingfrom both components integration will be able to produceperformance assessment of lecturer objectively. Themethod to proceed the assessment was Weighted Product(WP). The examined data of the lecturers were theBrawijaya University lecturers’ data. The finalexamination data was conducted by taking the datarandomly from 20 Brawijaya University lecturers. Thefinal output from this Decision Support System is thelecturers which are selected from three categories, whichare, less, normal, and good. It is expected that DecisionSupport System is able to categorize the standard eligiblelecturer (Normal/medium category), and the lecturersurpassing the standard (good category).